The State-of-the-Art Propagation and Breeding Techniques for Horticulture Crops - Roberto, Sergio Ruffo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The aim of this Special Issue is to present the latest advances in new horticultural propagation and breeding methods. The Special Issue "The State-of-the-Art Propagation and Breeding Techniques for Horticulture Crops" brings together some of the latest research results of new techniques in this field. It presents twelve original papers, which deal with a wide range of research activities.